cAMP-response element-binding protein and heat-shock protein 70 additively suppress polyglutamine-mediated toxicity in Drosophila. - Iijima-Ando, K.; Wu, P.; Drier, E.A.; Iijima, K.; Yin, J.C. (Proceedings of the National Academy of Sciences of the United States of America, 2005)
Gene-specific expansion of polyglutamine-encoding CAG repeats can cause neurodegenerative disorders, including Huntington's disease. It is believed that part of the pathological effect of the expanded protein is due to transcriptional dysregulation. Using Drosophila as a model, we show that cAMP-response element-binding protein (CREB) is involved in expanded polyglutamine-induced toxicity. A mutation in the Drosophila homolog of CREB, dCREB2, enhances lethality due to polyglutamine peptides (polyQ), and an additional copy of dCREB2 partially rescues this lethality. Neuronal expression of expanded polyQ attenuates in vivo CRE-mediated transcription of a reporter gene. As reported previously, overexpression of heat-shock protein 70 (Hsp70) rescues polyglutamine-dependent lethality. However, it does not rescue CREB-mediated transcription. The protective effects of CREB and heat-shock protein 70 against polyQ are additive, suggesting that targeting multiple pathways may be effective for treatment of polyglutamine diseases.